Unveiling Ideology In The Interpretation Of The Qur’an In Tafsir al-Wa’ie - Fatih Akbar Nur (Yayasan Pesantren Mahasiswa An-Nur, 2023)
The development of studies on interpretation must have experienced many developments, including in Indonesia. This can be seen from various works of interpretation born in the archipelago with many kinds of patterns and methods used by the mufassir. One of the works of Tafsir in Indonesia is the result of the thoughts of Hizb at-Tahrir, an Indonesian activist, namely Rokhmat S. Labib, who authored Tafsir al-Wa'ie. The tafsir is quite thick with the views of his organization that carries the mission of the Khilāfah al-islāmiyyah; the themes raised are very ideological. In interpreting the verses of the Qur'an, they tend to be textual. The thought of Rokhmat S. Labib contained in his tafsir work criticizes the understanding of Muslims, which is mainly contaminated with Western cultures, such as pluralism of religion, religious freedom, the idea of human rights that is so broad, and so on. This interpretation can be classified as an affirmative-era interpretive work with ideological reason when viewed from its epistemological structure.